MANFAAT REBOZO MENGGUNAKAN TEKNIK SHAKE THE APPLE UNTUK MENGURANGI RASA NYERI DAN LAMA KALA I FASE AKTIF PADA IBU BERSALIN DI KLINIK MUTIARA KASIH PURWAKARTA TAHUN 2021 - Teti Yuli Handayani (Fakultas Ilmu Kesehatan Unsika, 2021)
Pain can be eliminated pharmacologically and non-pharmacologically. Non-pharmacological method by giving Rebozo. This study aims to determine the effect of the Rebozo Shake The Apple Technique on reducing pain scale in labor and the length of the first stage of the active phase of labor at Polindes Alfiyah, Kalijati District, Kab. Subang in 2021. This study uses a pre-experiment (quasi-experimental) with the approach of The One Group Pretest-Posttest Design. This research was conducted from July to April 2021. The type of data used in this study used primary and secondary data. The sample in this study were 30 respondents, using total sampling technique. The method of data analysis used the MannWhitney non-parametric statistical analysis technique. The results of the research on the Rebozo Shake The Apple technique on the duration of the 1st stage of the active phase in multigravida mother delivery, because the p value > 0.05, so 'Ho' was accepted. multigravida. Researchers suggest for health services to be a facilitator in laboring mothers who experience pain so that the birthing mother can carry out the delivery process to be comfortable. Keyword : Rebozo Shake The Apple Technique, labor, active phase I pain